Disease Pattern of Early Neonatal Deaths: Household Health Survey 1992 - L. Ratna Budiarso; Agustina Lubis; Sarimawar Djaya; C.M. Kristanti (Indonesian Pediatric Society, 1997)
In 1992, socio-economic survey was conducted and early neonatal deaths in the sample were recorded and investigated through a verbal autopsy to idendfy the causes of death. Main diseases and conditions in the fetus or infants, and the main maternal conditions affecting the fetus and infant were analyzed. The prevalent disÂeases or conditions in fetus or infants as the main cause of early neonatal deaths were hypoxia (43%) and premature births (30%). Obstetric complications affected 36% early neonatal deaths, and maternal conditions affected 25% early neonatal deaths. Complications during pregnancy and delivery frequently cause premature births and hypoxia or asphyxia to the newborn infant. Comprehensive neonatal care should be available in all health centers, delivery homes, and hospitals.